Pediatric otolaryngology in the COVID-19 era (2020)
While the majority of attention to the healthcare impact of COVID-19 has focused on adult first responders and critical care providers, the pandemic has had a profound effect on the entire healthcare industry, including the pediatric otolaryngology community. The objective of this article is to highlight the unique ramifications of COVID-19 on pediatric otolaryngology, with a focus on the immediate and potential long-term shifts in practice. Specifically, the article is divided into three sections (Care for the patient, Care for the practitioner, Care for the Practice) and details the unique effects of the pandemic on the pediatric otolaryngology specialty.